A solar thermal driven ORC-VFR system employed in subtropical Mediterranean climatic building. (1st July 2022) - Gilani, Hooman Azad; Hoseinzadeh, Siamak; Esmaeilion, Farbod; Memon, Saim; Garcia, Davide Astiaso; Assad, Mamdouh El Haj
Abstract: This paper investigates the configuration of solar thermal collector driven organic Rankine cycle (ORC) utilized to power air-conditioning system of the two-story office building in Paralimni, Cyprus, through a Variable-Refrigerant-Flow (VRF) system. The reason to choose this Mediterranean climate of Paralimni, Cyprus, is due to its higher dependency on fossil fuels compared to many other countries in the EU and with a high potential of harnessing solar irradiations and demand for air-conditioning (AC) loads. This location is categorized as warm temperate zones, subtropical climates and is placed in the subcategory of Mediterranean climates with humid winters and dry summers according to climatic zone, highly demanding for air conditioning. Based on the climatic data of the study area, this system can make an effective performance. Modeling the building and estimating the AC system power consumption is carried out in the DesignBuilder. Designing the organic Rankine cycle is done with EES. A solar hot water system is designed with TRNSYS to supply the required mass flow rate of water at the desired temperature of 95 °C. In this climate, the annual surface irradiation rate is 1, 793 kWh/m 2 whilst the AC energy requirement of a two-story building is 7, 909 kWh. The employed ORC with an internal heat exchanger is designed with a constant output rate of 3.920 kW, which delivers a total of 8, 154 kWh yearly. The required heat input of the ORC is supplied by a solar hot water system, employing evacuated tube collectors. The solar system consumes a 454 kWh auxiliary heating rate per year to deliver the desired mass flow rate and outlet temperature for the ORC. As a result, the designed solar-driven ORC delivers a net of (8, 154 – 454) kWh = 7, 700 kWh energy each year, meaning 7, 700 kWh energy saving per year, equal to 97% of VRF annual energy demand. This amount of yearly energy saving yields 2, 010 USD yearly capital saving as the reward of investment in this system, and defining a 20-year project, the implementation of this solar-driven power generation system at the end of the project's lifetime would save 25, 049 USD. Graphical abstract: Image 1 Highlights: A new configuration of solar-driven ORC to power AC system of building Cyprus is proposed. It achieves 7700 kWh energy savings per year, equivalent to 97% of VRF annual energy demand. Energy yields 2010 USD of yearly capital saving as the reward of investment in this system. The deployment of this system at the conclusion of the project's 20-year lifespan could save 40, 200 USD.